2016
DOI: 10.5665/sleep.6026
|View full text |Cite
|
Sign up to set email alerts
|

Polysomnographic Measurement of Sleep Duration and Bodily Pain Perception in the Sleep Heart Health Study

Abstract: Shorter TST among all subjects and shorter SWS time in men was associated with "moderate to severe pain." REM sleep time was not associated with bodily pain perception in this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…13,14,36 A recent population-based study also showed that short total sleep times are associated with reports of moderate to severe pain. 45 Further, experimental data have demonstrated that sleep restriction reduces pain thresholds, which supports the observed relationships between insufficient sleep and increased pain sensitivity in experimental and population-based studies. 18,20,24,26,31,33,36,41 Improving sleep quantity and/or quality also reduces pain sensitivity in healthy participants 32 and pain severity in chronic pain patients.…”
Section: Introductionsupporting
confidence: 54%
“…13,14,36 A recent population-based study also showed that short total sleep times are associated with reports of moderate to severe pain. 45 Further, experimental data have demonstrated that sleep restriction reduces pain thresholds, which supports the observed relationships between insufficient sleep and increased pain sensitivity in experimental and population-based studies. 18,20,24,26,31,33,36,41 Improving sleep quantity and/or quality also reduces pain sensitivity in healthy participants 32 and pain severity in chronic pain patients.…”
Section: Introductionsupporting
confidence: 54%
“…Haack et al [30] conducted a study and found that activation of the prostaglandin E2 (PGE2) system appeared to be a potential mediator of increased spontaneous pain in response to insufficient sleep. Weingarten et al conducted a population-based study [31], and the authors concluded that short TSTs were associated with reports of moderate to severe pain. Odegard et al [32] concluded that sleep restriction reduced the central nervous system (CNS) response to pain, while some of the subjective pain measures indicated hyperalgesia.…”
Section: Discussionmentioning
confidence: 99%
“…37,54 Apart from problems with sleep initiation and maintenance, sleep-disordered breathing, 2 restless legs syndrome, 27 and narcolepsy, 17 are also more common among people with pain disorders than in pain-free individuals, although there is little evidence that sleep architecture differs in people with pain. 6,57 Longitudinal studies show that although disturbed sleep and pain have bidirectional relationships, the effect of sleep disturbance on pain development is greater than the effect of pain on sleep disturbance. 21 Moreover, the extent of sleep disturbance predicts sensitivity to experimental pain 52 and intensity of clinical pain 1 in a dose-response manner.…”
mentioning
confidence: 99%